Physicalism and moral responsibility: presentation of derivative consequence argument - B. V. Faul (Омский научный вестник: Серия "Общество. История. Современность")
In this paper, the author introduces the derivative consequence argument, which aims to demonstrate that moral responsibility is impossible in the world where physicalism and the strong realism about the laws of nature are both true. The basic intuition of the argument is that if the laws of nature determine the events, then nobody can be responsible for those events, because nobody is responsible for the laws of nature. This intuitive idea is formalized in the categories of derivative causation and motion. This argument is compatible with determinism and indeterminism, and all types of physicalism